THEORETICAL RESPONSES TO THE QUESTIONS OF ONE LAW FOR ONE SOCIETY AND MULTIPLE LAWS FOR MULTIPLE SOCIETIES - Evita Vibriana Wulandari; Zainal Arifin (ZILLZELL MEDIA PRIMA, 2023)
The Indonesian legal system is a combination of several religious, customary and European legal systems, especially the Dutch as a nation that once colonized Indonesia for 3.5 centuries. So, it is not surprising that their inherited civilization includes the legal system. Living law refers to the laws that are still valid and applied in society, including customary law, religious law, and positive law. This law can coexist with various other laws, such as civil, constitutional and criminal law, which apply according to the context and issues that arise in society. Therefore, it is important to understand and accommodate the various sources of law in a society to achieve justice and order. In the Indonesian context, the applicability of law to the life of society and the state involves various factors, including public awareness, lawmaking, and juridical, sociological and philosophical foundations. Indonesia's legal system is a combination of several legal systems, including religious, customary and state law. This shows the complexity in the application of law in society, which requires a comprehensive understanding and accommodation of various sources of law to achieve legal objectives, such as order, justice and security.